2022
DOI: 10.1177/11206721221136324
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in BBS genes and clinical characterization of Chinese families with Bardet–Biedl syndrome

Abstract: Purpose Bardet–Biedl syndrome (BBS) is a rare autosomal-recessive inherited disorder characterized by multisystem anomalies. The objective of this study was to detect and analyse pathogenic variants in four Chinese families with BBS. Methods Comprehensive clinical examinations were performed to investigate and evaluate the phenotypes of the affected individuals from four families. Genomic DNA was extracted from peripheral blood. Next-generation sequencing (NGS) was performed for four families, and the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Except for one case without detailed data of variant, 19 BBS2 patients from 12 families were reported ( Xing et al, 2014 ; Chen et al, 2017 ; Li et al, 2017 ; Ding et al, 2018 ; Dan et al, 2020 ; Huang et al, 2021 ; Meng et al, 2021 ; Tang et al, 2022 ; Tao et al, 2022 ; Wei et al, 2022 ), including 12 (63.16%) compound heterozygous variants and 7 (36.84%) homozygous variants. Unlike report from the United States ( Guardiola et al, 2021 ), which reported hot spot variants in BBS1 and BBS7 , a total of 15 variants were reported in our series.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for one case without detailed data of variant, 19 BBS2 patients from 12 families were reported ( Xing et al, 2014 ; Chen et al, 2017 ; Li et al, 2017 ; Ding et al, 2018 ; Dan et al, 2020 ; Huang et al, 2021 ; Meng et al, 2021 ; Tang et al, 2022 ; Tao et al, 2022 ; Wei et al, 2022 ), including 12 (63.16%) compound heterozygous variants and 7 (36.84%) homozygous variants. Unlike report from the United States ( Guardiola et al, 2021 ), which reported hot spot variants in BBS1 and BBS7 , a total of 15 variants were reported in our series.…”
Section: Resultsmentioning
confidence: 99%
“…Among 10 BBS10 patients ( Lin et al, 2018 ; Wang et al, 2018 ; Tao et al, 2020 ; Liu et al, 2021 ; Li et al, 2022a ; Li et al, 2022b ; Dong et al, 2022 ; Lu et al, 2022 ; Tao et al, 2022 ; Yan et al, 2022 ), 7 had compound heterozygous variants and 3 had homozygous variants. A total of 11 variants were also reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation